2018
DOI: 10.1096/fj.201700891r
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide prevents NF‐κB from recruiting p300 and binding to the inos promoter in diabetic nephropathy

Abstract: C-peptide (CP) has demonstrated unique beneficial effects in diabetic nephropathy (DN), but whether and how CP regulates NF-κB and its coactivator, p300, to suppress inducible iNOS and antagonize DN are unknown. iNOS expression, NF-κB nuclear translocation, colocalization and binding of NF-κB to p300, binding of NF-κB to the inos promoter, and the bound NF-κB, p300, and histone 3 lysine 9 acetylation (H3K9ac) at binding sites were measured in high glucose-stimulated mesangial cells. We evaluated pathologic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
(68 reference statements)
0
21
0
1
Order By: Relevance
“…We also found NFκB-dependent recruitment of p300 to the enhancers extending our understanding of the mechanisms regulating p300 recruitment (Ong and Corces, 2011). CBP and p300 have been examined as scaffolding proteins supporting NFκB-regulated promoters (Kamitani et al, 2011; Li et al, 2018; Mukherjee et al, 2013). Thus, interactions between NFκB and p300 are well described at promoters.…”
Section: Discussionmentioning
confidence: 99%
“…We also found NFκB-dependent recruitment of p300 to the enhancers extending our understanding of the mechanisms regulating p300 recruitment (Ong and Corces, 2011). CBP and p300 have been examined as scaffolding proteins supporting NFκB-regulated promoters (Kamitani et al, 2011; Li et al, 2018; Mukherjee et al, 2013). Thus, interactions between NFκB and p300 are well described at promoters.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic status, high glucose, AGEs, and oxidative stress could simultaneously induce the activation of NF- κ B, a known transcriptional signature of inflammation [18]. Through recruiting p300, NF- κ B triggers the activation of downstream effector iNOS, a promoter of oxidative stress and inflammation that causes extensive nitrotyrosine (NT) in proteins [159]. Genetic and pharmacological inhibition of NF- κ B signaling prevent age-associated diseases [160162] including diabetic nephropathy [159] and natural aging [163, 164].…”
Section: The Mechanisms Of Cellular Senescence In Diabetic Nephropmentioning
confidence: 99%
“…Advanced glycation end products increased NF-kappaB-binding activity to the promoter of ET-1 thus to increase ET-1 expression [28]. Researchers reported that C-peptide protected DN by preventing NF-kappaB from recruiting p300 and binding to the inos promoter [29]. Kolati et al demonstrated that NF-kappaB inhibitor BAY 11-7082 ameliorated DN by inhibiting renal inflammation and oxidative stress [30].…”
Section: Discussionmentioning
confidence: 99%